Clinically stable disease is associated with a lower risk of both income loss and disability pension for patients with multiple sclerosis. Issue 1 (14th November 2019) - Chalmer, Thor Ameri; Buron, Mathias; Illes, Zsolt; Papp, Viktoria; Theodorsdottir, Asta; Schäfer, Jakob; Hansen, Victoria; Asgari, Nasrin; Skejø, Pernille Bro; Jensen, Henrik Boye; Sørensen, Per Soelberg; Magyari, Melinda
Abstract : Objective: To assess the risk of losing income from salaries and risk disability pension for multiple sclerosis patients with a clinically stable disease course 3 years after the start of disease-modifying therapy (DMT). Methods: Data from the Danish Multiple Sclerosis Registry were linked to other Danish nationwide population-based databases. We included patients who started treatment with a DMT between 2001 and 2014. Patients were categorised into a clinically stable group (No Evidence of Disease Activity (NEDA-2)) and a clinically active group (relapse activity or 6-month confirmed Expanded Disability Status Scale worsening). Outcomes were: (1) loss of regular income from salaries and (2) a transfer payment labelled as disability pension. We used a Cox proportional hazards model to estimate confounder-adjusted HRs, and absolute risks were plotted using cumulative incidence curves accounting for competing risks. Results: We included 2406 patients for the income analyses and 3123 patients for the disability pension analysis. Median follow-up from index date was 5 years in both analyses. The NEDA-2 group had a 26% reduced rate of losing income (HR 0.74; 95% CI 0.60 to 0.92). HRs were calculated for 5-year intervals in the disability pension analysis: year 0–5: a 57% reduced rate of disability pension for the NEDA-2 group (HR 0.43; 95% CI 0.33 to 0.55) and year 5–10: a 36% reduced rate (HR 0.64; 95% CI 0.40 to 1.01). Conclusion: Clinically stable disease course (NEDA-2) is associated with a reduced risk of losing income from salaries and a reduced risk of disability pension.